Transcriptional progressive patterns from mild to severe renal ischemia/reperfusion-induced kidney injury in mice - Lai, Dong; Wang, Lei; Li, Jia-Rui; Chen, Chen; Zhao, Wen-Lei; Yuan, Qing; Ma, Xin; Zhang, Xu (Frontiers in Genetics, 2022)
The renal ischemia/reperfusion (I/R)-induced acute kidney injury incidence after nephron-sparing surgery for localized renal tumors is 20%, but the biological determinant process of postoperative AKI remains unclear. Using Gene Expression Omnibus database (GSE192883) and several bioinformatics analyses (time series analysis, gene set enrichment analysis, dynamic network biomarker analysis, etc), combined with the establishment of the I/R model for verification, we identified three progressive patterns involving five core pathways confirmed using gene set enrichment analysis (GSEA) and six key genes (S100a10, Pcna, Abat, Kmo, Acadm, and Adhfe1) verified using quantitative polymerase chain reaction (qPCR). The dynamic network biomarker (DNB) subnetwork composite index value is the highest in the 22-min ischemia group, suggesting the transcriptome expression level fluctuated sharply in this group, which means 22-min ischemia is an critical warning point. This study illustrates the core molecular progressive patterns from mild to severe I/R kidney injury, laying the foundation for precautionary biomarkers and molecular intervention targets for exploration.In addition, the safe renal artery blocking time of nephron-sparing surgery that we currently accept may not be safe anymore.